Language and text in adjudication and dispute settlement in administrative tribunals and related settings - Jenkings, Kenneth Neil (1997)
This thesis has four main objectives; a) to provide an understanding of Legal Aid Appeals Tribunals, from a description of individual cases and the activities that occur therein, focusing in the main on those at which an appellant and/or their representative is present; b) to explore the use of documentation in the tribunal practices of tribunal panel members, legal aid clerks, appellants and their representatives; c) to explore the possibilities that post-analytic ethnomethodology as the adopted research methodology allows, and to clarify what this radical research 'programme' entails; and d) taking legal positivism as an epistopic to explore its possible ethnomethodological respecification in light of the descriptions of practice in legal aid tribunals. Although this thesis explores the possibility of post-analytic descriptions it is not a theoretical investigation into post-analytic ethnomethodology, but an empirical investigation of phenomena of legal aid tribunals which allows an exploration of the practical application of post-analytic ethnomethodology. Nevertheless, some clarification is attempted of just what a post-analytic ethnomethodology may entail. Used in conjunction with the description of the use of texts in legal tribunals, the investigation of epistopics, though not a common research practice does here help develop our understanding of the situated nature of legal practical, legal decision making, and legal objectivity. In a wider sense this approach highlights an argument made throughout this research, that texts are both significant and researchable as they are utilised in everyday practices, and do not have to be research solely with reference to an isolated reader and an isolated content.